FAKTOR-FAKTOR YANG MEMPENGARUHI INCOME SMOOTHING PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Felinda Yoe; Rini Tri Hastuti (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This research aims at how the role of the profitability and financial leverage on income smoothing, and the effect of firm size toward income smoothing on manufacturing company listed on the Indonesia Stock Exchange during 2017-2019. Sample was selected using purposive sampling method and the valid data was 71 companies. Data processing techniques using multiple regression analysis which helped by Eviews 11 program (Econometric Views) and Microsoft Excel 2018. The results of this study indicate that profitability don’t have a significant influence on income smoothing and financial leverage have a significant influence on income smoothing, and firm size decreases influence on income smoothing. The implication of this study is the need to increase the role of the profitability and financial leverage upon any firm size that will increase the detection of applying income smoothing practice in company which will bring a good signal for investors to be more careful in investing.